Signals from the future: Exploring implications for drug policies - L. Gremeaux (Lisbon Addiction. European Conference on Addictive Behaviours and Dependencies, 2022)
Building futures literacy in the drug policy domain contributes to enhanced preparedness and will support more proactive drug policy responses. As part of the DRUG-PREP project, this workshop aims to introduce the participants to basic foresight approaches and mutual learning practices for exploring the dynamics of future uncertainties and change in the drugs field. The overall aim of DRUG-PREP is to contribute to enhanced preparedness and resilience of EU countries’ drug surveillance systems and effective policy making. To this end, conference participants form an important component for this foresight project by bringing along the required international perspectives and experience from diverse domains in current drug policy, practice and science. In a first step, participants will be introduced to key drivers, predetermined elements and critical uncertainties that form the basis for shaping the future drugs policy area, which will have been mapped by DRUG-PREP via horizon scanning prior to the workshop. A participatory consultation process will then be facilitated for in-depth exploration of subsequent implications for European drug policies. A distinction will be defined between drivers and trends with a certain and uncertain outcome. By mapping when and how emerging issues and themes are likely to impact on the policy area, a shared sense of purpose is built and the requirements for mitigating threats and seizing opportunities are marked. The identified insights of high impact for the future EU drug policy area will serve as a precursor for the next research stage in the DRUG-PREP project, which involves strategic planning through further developing country-specific policy implications, visioning change and roadmapping towards an alternative future for drug policies in 2030+. The strength of this interactive session is the twofold return by creating foresight capacity building with the workshop participants, as well as the active contribution that will be injected into the overall DRUG-PREP foresight exercise.
Keywords: DRUG-PREP; Foresight; illicit drugs; preparedness